MELALUI METODE EKSPERIMEN DAPAT MENINGKATKAN HASIL BELAJAR SISWA KELAS VIIIA PADA MATERI CAHAYA PELAJARAN IPA DI SMPN 1 MEUREUDU - Ridwan Ridwan (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2022)
This study aims to determine the increase in student learning outcomes for class VIII_A light science subjects, especially physics through experimental methods at SMPN 1 Meureudu. The research method used is classroom action research (CAR) which consists of 2 cycles. The research subjects were class VIII-A students in the 2018/2019 academic year as many as 32 students. Data analysis used comparative descriptive analysis techniques by comparing the initial conditions with the results achieved in each cycle, and qualitative descriptive analysis of observations by comparing the results of observations and reflections in cycle I and cycle II. With the experimental method on light material for the 2018/2019 school year. The results of the first cycle of learning only 15 students completed (46.9 %), with the acquisition of an average value of student activities of 58.9% and the ability of teachers to carry out PBM 63.8% including the sufficient category. After the second cycle, it turned out that there was an increase in the number of students who completed as many as 23 people (71.9%) of the total number of 32 students with an average acquisition of student activity of 72.8%. Furthermore, the ability of teachers in managing PBM has increased to 77.7%. Thus, most of the students of class VIII-A SMPN 1 Meureudu experienced an increase in learning outcomes in science, especially physics on light material.Keywords: learning outcomes, experimental method, and Light